Updates on Laryngology - Singh Gendeh, Balwant (IntechOpen, 2023)
This book presents selected topics on the larynx and related problems, providing insight into recent advances in the field. Airway and speech are of critical importance in our daily lives and contribute to our personal well-being and safety as well as our communication with others. However, it is only when disease or injury impairs its function that we appreciate the relevance of the larynx. This book presents new clinical and research developments as well as future perspectives on airway-related problems and lesions. Chapters discuss laryngeal examination, laryngo-pharyngeal reflux, vocal cord paralysis, laryngeal leukoplakia, and much more.